Surveillance Spy Robot with Wireless Night Vision Camera and Metal Detection (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Saving people’s lives and ensuring safety are very important in fact very essential. A Bluetooth controlled spy robot is an Arduinobased bot which is been supervised and handled using an android application. A spy robotic vehicle is an human replacement which is controlled by the human itself. In this paperthe most important objective is to develop the robotic vehicle to keep the track of all the unusual activities in the border regions, and reduce the intervention of intruders. This spy robot contains a wireless CCD camera which is used to transmit the live video footage of the war field environment to prevent the loss and damages of armed forces. This spy robot has features including metal detection and identification of the explosives in the restricted areas and it gives both latitude and longitude position of the explosives identified using gsm module.